PEMANFAATAN LIMBAH KULIT JAGUNG DAN AMPAS TEBU SEBAGAI KERTAS KEMASAN RAMAH LINGKUNGAN - Oktaffi Arinna Manasikana, Oktaffi (Jurnal Zarah, 2019)
The increasing need for paper and the demands of the community for environmentally friendly technology is increasing, causing the need for a large supply of paper raw materials to the paper industry sector. The limited supply of raw materials for paper production caused by environmental issues causes the price of paper to rise. The content of bagasse is cellulose, pentosan, lignin and others, while the content of corn husk consists of ash, lignin, cellulose, and hemicellulose. These components can be used as paper making materials because they have high cellulose content. The resulting paper is expected to be used as an environmentally friendly packaging material. The purpose of this study is to determine the potential of corn husk waste and bagasse as an environmentally friendly packaging paper material, as well as to analyze the comparison between the composition of corn husk and sugarcane bagasse to produce the highest quality packaging paper . The test samples used in this study are tensile, elasticity and biodegradability tests. The results showed that corn husk waste and sugarcane bagasse have the potential to be environmentally friendly packaging paper. Paper with the best quality is compared to 25% corn husk and 75% bagasse with a tensile test of 14.8 N elasticity test of 13.33% and 50% biodegrated paper area.